Perancangan Konstruksi Profil Pada Kapal General Cargo Dengan Menggunakan Metode Ship Comparative - Rahmahdani Japri (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2021)
General cargo ship is a ship that carries various kinds of cargo in the form of goods. The goods transported are usually packaged goods. The main size of the ship was obtained using the comparative regression method which was based on the data of the 2 comparison ships obtained from the Korean Register of Shipping (KRS). In this study, a general cargo ship profile construction design is planned which is designed according to the main size of the ship in accordance with the rules of the Indonesian Classification Bureau Rules. From the planning results obtained for ships with a capacity of 17000 DWT obtained ship dimensions with length over all (LOA) 153.45 m, length between prependiculars (LBP) 144.24 m, Length on load waterline (LWL) 147.85 m, width (B) ) 25.27 m, height (H) 13.5 m, draft (H) 9.52 m, speed (V) 14.75 knots. This comparison method facilitates ship design with more accurate results.